Technology in Higher Education: An Exploratory Study to Investigate Teachers' Ideas and Perspectives - Nicchia, Elisabetta; Parmigiani, Davide; Murgia, Emiliana (Formazione & insegnamento, 2024)
University teaching, thanks to the thrust of Faculty Development, is redesigning its learning processes to meet the needs of its increasingly diverse students and to make its teaching practices active, formative and vocational. Technologies in this perspective can be an effective support. This study presents the results of an exploratory research conducted through a semi-structured interview with 30 participants, lecturers at the University of Genoa. The aim was to understand if and how technologies are used in teaching, investigating chosen tools and activities, strengths and limitations of technological devices, aspects of the learning process they activate and experiences of formative evaluation practices. The analysis of the data revealed a variability of tools and practices according to disciplines and contexts. The teachers emphasised, in particular, the need to implement digital literacy practices and the need to reflect on formative and student-centred assessment practices.